Gobierno corporativo en el sector bancario de una economía emergente - Lizarzaburu, Edmundo R. (2019)
The purpose of this research is to measure the relationship between the application of good corporate governance practices in relation to the economic value of listed banks in an emerging market such as the Lima Stock Exchange, given the growing importance of corporate governance, and in the absence of empirical evidence on banks in emerging markets. The methodology used employs a model that evaluates the Tobin's Q, leverage ratios, portfolio quality, efficiency and return on assets (ROA) and the dichotomous variable with respect to the incorporation into the Good Corporate Governance Index of the stock exchange. Lima, considering a temporality from 2011 to 2016.